The relationship between ultra-processed food intake and cardiometabolic risk factors in overweight and obese women: A cross-sectional study - Hosseininasab, Dorsa; Shiraseb, Farideh; Noori, Sahar; Jamili, Shahin; Mazaheri-Eftekhar, Fatemeh; Dehghan, Mahshid; da Silva, Alessandra; Bressan, Josefina; Mirzaei, Khadijeh (Frontiers in Nutrition, 2022)
Background: Cardiovascular diseases (CVDs) are the leading cause of death globally. Based on recent studies, one of the factors that can have detrimental effects on CVD is the consumption of ultra-processed foods (UPFs). The current study investigated the relationship between UPF intake and cardiometabolic risk factors among Iranian women. Methods: The current cross-sectional study was conducted on 391 women aged 18-65 years with a body mass index (BMI) ≥25 kg/m2. Dietary intake was assessed using a 147-item food frequency questionnaire (FFQ). Anthropometric and biochemistry parameters were also collected. UPFs were identified using the NOVA classification. Results: In the present study, women had a mean (standard deviation) age of 36.67 (9.10) years, and the mean BMI of 31.26 (4.29) kg/m2. According to our findings, there was a significant association between UPF consumption and transforming growth factor (TGF) (β: 0.101, 95% CI: 0.023, 0.180, P-value= 0.012), atherogenic coefficient (AC) (β: 0.011, 95% CI: 0.001, 0.032, P-value= 0.034), visceral fat level (VFL) (β: 0.006, 95% CI: -0.017, 0.029, P-value= 0.076), and the quantitative insulin sensitivity check index (QUICKI) (β: -3.775, 95%CI: 0.001, 0.001, P-value= 0.042). Conclusion: In conclusion, an increase of one gram of UPFs consumption is associated with an increase in TGF, AC, and VFL, but with a decrease in QUICKI. Despite this, further experimental studies are necessary to draw a more definite conclusion and disentangle the mechanisms by which UPFs may affect health.